2018
DOI: 10.1155/2018/7070868
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Hybrid Approach of Finite Element Method, Artificial Neural Network-Based Multiobjective Genetic Algorithm for Computational Optimization of a Linear Compliant Mechanism of Nanoindentation Tester

Abstract: This paper proposes a new evolutionary multiobjective optimization technique for a linear compliant mechanism of nanoindentation tester. The mechanism design is inspired by the elastic deformation of flexure hinge. To improve overall static performances, a multiobjective optimization design was carried out. An efficient hybrid optimization approach of central composite design (CDD), finite element method (FEM), artificial neural network (ANN), and multiobjective genetic algorithm (MOGA) is developed to solve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 31 publications
(37 reference statements)
0
18
0
Order By: Relevance
“…Figure 5 shows the optimal solution sets of − f 1 (x) and − f 2 (x). e results revealed that NSGA-II has significant advantages over other algorithms in optimal performances [20]. Specifically, the negative number of maximum equivalent stress and minimum contact pressure from NSGA-II is smaller than that from MOSA and MOPSO.…”
Section: Nsga-iimentioning
confidence: 94%
See 1 more Smart Citation
“…Figure 5 shows the optimal solution sets of − f 1 (x) and − f 2 (x). e results revealed that NSGA-II has significant advantages over other algorithms in optimal performances [20]. Specifically, the negative number of maximum equivalent stress and minimum contact pressure from NSGA-II is smaller than that from MOSA and MOPSO.…”
Section: Nsga-iimentioning
confidence: 94%
“…Equations (21)∼(25) are solved using NSGA-II, MOSA, and MOPSO algorithm. Among these three algorithms, NSGA-II setting: the population number is 1000, the variation rate is 0.1, and the crossing rate is 0.85; MOSA setting: the Boltzmann coefficient is 1, the maximum internal loop number is 1000, and the cooling coefficient is 0.99; MOPSO setting: the population number is 1000 and the nearest population is 2. e certain type of the shrink disk is designated as an example, and the three algorithms are used to run 20 times independently [20]. e minimum mass obtained by these three algorithms is the same f 3 (x) � 960.970.…”
Section: Nsga-iimentioning
confidence: 99%
“…The optimization experienced the main steps, such as design a mechanical structure, define design variables and objective functions, build 3D model, evaluate initial performances, and establish the numerical experiments using response surface. These steps can be found in detail by [26].…”
Section: Hybrid Optimization Algorithmmentioning
confidence: 99%
“…This algorithm was proposed for multiobjective optimization problem in this study because it can converge to the global Pareto solutions. This algorithm helped to seek a Pareto-optimal set for multiple objective optimization [26]. The MOGA was a variant of the Nondominated Sorted Genetic Algorithm-II (NSGA-II) that replied on controlled elitism concepts.…”
Section: Hybrid Optimization Algorithmmentioning
confidence: 99%
“…The success of using these “intelligent” paradigms in modeling dynamic systems is due to the little knowledge required to perform modeling (only a reasonable amount of data is required) compared to other forms of analytical modeling, and also because they are naturally nonlinear models. Among these “intelligent” techniques used for nonlinear dynamic modeling [11,12], one of the most used is artificial neural networks. The use of artificial intelligence in dynamic modeling based on data is sometimes referred to as soft sensors.…”
Section: Introductionmentioning
confidence: 99%